How does Environmental Law View Sustainable Ecological Development in Indonesia? - Dadi Dadi (LEGAL BRIEF, 2022)
The problem of natural resources and the environment has developed into a crisis experienced by various countries in the world, including Indonesia. The damage to the global environment that has a serious impact on the sustainability of human life and development must be addressed as early as possible, so that the effect does not spread to the growth cycle of future generations. One of the efforts that can be taken as a reaction to the current environmental management crisis is to start developing an environmental movement based on an ecological approach or sustainable development. This study uses a normative juridical approach, which is an approach that is based on legislation, by examining all laws and regulations related to the legal issue that the researcher is looking for, while the results of this study explain that the enactment of Law no. 32 of 2009 concerning Environmental Protection and Management (UU-PPLH) in Indonesia is a tangible manifestation of the government's and community's concern in realizing the welfare of the people, which began through the establishment of environmental law and is an instrument of state administration in the efficient management of natural resources. The concept of ecology which is based on the existence of legal order and values ??that requires policy changes in overcoming environmental crises or emergencies due to exploitation of environmental resources that ignores aspects of sustainability and environmental carrying capacity does require encouragement from all parties so that all management processes and the application of sanctions can be implemented. The sanctions can be realized in various concrete actions and actions, the environment as a forum for management policies various natural resources that exist, contain legal rules that are in accordance with the principles of Humanity is intended to optimize the benefits of natural resources (SDA) and human resources to be further harmonized in an ecological concept that is beneficial for human survival.